Potential Applications of Nanotechnology in Urological Cancer - He, Ming-Hui; Chen, Li; Zheng, Ting; Tu, Yu; He, Qian; Fu, Hua-Lin; Lin, Ju-Chun; Zhang, Wei; Shu, Gang; He, Lili; Yuan, Zhi-Xiang (Frontiers in Pharmacology, 2018)
Nowadays, the potential scope of nanotechnology in uro-oncology (cancers of the prostate, bladder, and kidney) is broad, ranging from drug delivery, prevention, and diagnosis to treatment. Novel drug delivery methods using magnetic nanoparticles, gold nanoparticles and polymeric nanoparticles have been investigated in prostate cancer. Additionally, renal cancer treatment may be profoundly influenced by applications of nanotechnology principles. Various nanoparticle-based strategies for kidney cancer therapy have been proposed. Partly due to the dilution of drug concentrations by urine production, causing inadequate drug delivery to tumor cells in the treatment of bladder cancer, various multifunctional bladder-targeted nanoparticles have been developed to enhance therapeutic efficiency. In each of these cancer research fields, nanotechnology has shown several advantages over widely used traditional methods. Different types of nanoparticles improve the solubility of poorly soluble drugs, and multifunctional nanoparticles have good specificity towards prostate, renal, and bladder cancer. Moreover, nanotechnology can also combine with other novel technologies to further enhance effectivity. As our understanding of nanotechnologies grows, additional opportunities to improve the diagnosis and treatment of urological cancer are excepted to arise. In this review, we focus on nanotechnologies with potential applications in urological cancer therapy and highlight clinical areas that would benefit from nanoparticle therapy.